2020
DOI: 10.1016/j.jep.2020.112662
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants used by ‘root doctors’, local traditional healers in Bié province, Angola

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 217 publications
(162 reference statements)
1
22
0
1
Order By: Relevance
“…In different countries located in Sub-Saharan Africa, the roots are generally utilized to treat infections and parasitic diseases, diseases of the digestive tract and as a dewormer as reported in some works (Waterman et al, 2010; Table 1). Hence, when reviewing the different studies performed at national levels on the ethnobotanical uses of S. spinosa, numerous studies have reported medicinal activities related to the aforementioned medicinal properties in Ghana, Benin, Burkina Faso, Mali and Kenya where it is also used to treat tuberculosis (Table 1; Asase et al, 2005;Bizimana et al, 2006;Bero et al, 2009;Ibrahim et al, 2014;Molander et al, 2014;Avakoudjo et al, 2019;Novotna et al, 2020). Besides, tuberculosis is most of the time associated with sexually transmitted diseases (STDs).…”
Section: Usages In Ethnomedicinementioning
confidence: 99%
See 3 more Smart Citations
“…In different countries located in Sub-Saharan Africa, the roots are generally utilized to treat infections and parasitic diseases, diseases of the digestive tract and as a dewormer as reported in some works (Waterman et al, 2010; Table 1). Hence, when reviewing the different studies performed at national levels on the ethnobotanical uses of S. spinosa, numerous studies have reported medicinal activities related to the aforementioned medicinal properties in Ghana, Benin, Burkina Faso, Mali and Kenya where it is also used to treat tuberculosis (Table 1; Asase et al, 2005;Bizimana et al, 2006;Bero et al, 2009;Ibrahim et al, 2014;Molander et al, 2014;Avakoudjo et al, 2019;Novotna et al, 2020). Besides, tuberculosis is most of the time associated with sexually transmitted diseases (STDs).…”
Section: Usages In Ethnomedicinementioning
confidence: 99%
“…Another example is S. cocculoides Baker (another African species) whose roots and fruits are up taken to treat STDs in Zambia; its roots are reduced to ashes to treat lymphogranuloma inguinale and its unripe fruit mixed with tea to treat erectile dysfunction in the same country. Besides, its roots alone are utilized to treat dysmenorrhea, new-born colic, cerebral ischemia, boils on legs, haemorrhage due to injury, and postpartum bleeding in Angola (Chinsembu et al, 2019;Novotna et al, 2020). A third example is S. panganiensis Gilg.…”
Section: Usages In Ethnomedicinementioning
confidence: 99%
See 2 more Smart Citations
“…ex DC. (Fabaceae) is an important medicinal plant as evidenced by the existence of its names in various local languages and high frequency of citation in ethnobotanical surveys [1][2][3][4]. e genus Erythrina derives from the Greek word "erythros," translated to mean red (a reflection of the showy red flowers of its various species).…”
Section: Introductionmentioning
confidence: 99%